Penguatan Karakter Peserta Didik Melalui Kegiatan Penyuluhan Mengenai Keteladanan Rasulullah SAW: Program Pengabdian Di SMA Negeri 15 Padang - Warlan Sukandar (CV. Multi Kreasi Media, 2025)
Character education is a crucial aspect in shaping students’ personalities, especially at the high school level, where adolescents are in the phase of identity formation. One effective approach to strengthening character is by introducing the exemplary qualities of the Prophet Muhammad (peace be upon him) as a universal role model. This community service program aimed to instill the values of the Prophet’s character in students through a counseling and educational session at SMA Negeri 15 Padang. The activity utilized a participatory and interactive counseling method, involving lectures, discussions, reflections, and role-play simulations. The session was attended by 824 students from grades X, XI, and XII, with an attendance rate of 97%. The results showed an increase in understanding of values such as honesty, responsibility, and empathy. Positive behavioral changes were also observed, including improved politeness, discipline, and active engagement in social interactions. Strong support from the school was evident, marked by the formation of Islamic study groups as a follow-up to the activity. Challenges faced included the large number of participants and limited time allocation, but these were overcome through appropriate delivery methods. This activity demonstrates that the exemplary character of the Prophet Muhammad (peace be upon him) is effective in strengthening students’ character and can serve as a model for Islamic value-based character education in other schools.